Ficus carica L. (Moraceae): An ancient source of food and health - Barolo, Melisa Isabel (2014)
Since early in the man history, common fig was appreciated as food and for its medicinal properties. This review explores some aspects about the importance of Ficus carica L., an amazing and ancient source of medicines and food. Topics regarding chemistry, biological activity, ethno-pharmacological uses, and its nutritional value are discussed, as well as the potential of the species as a source of new and different chemical scaffolds. Very important in the past, appreciated in our time and extremely promising in the future, F. carica represents an interesting example of healthy foods and bioproducts